Der Sturz Chruschtschows: ein Auszug aus den Memoiren des chinesischen Diplomaten Wu Xiuquan - Kampen, Thomas (Asien, 1989)
This is the translation of an extract from the memoirs of the Chinese diplomat Wu Xiuquan covering the events after Chrustchev's downfall in 1964. The detailed description of the gradual deterioration of Chinese Soviet relations is of particular interest. Wu criticizes the Soviet leader ship fact that might have been the reason for restricting this part of the memoirs only to limited readership. (Red.)
Elektronische Reproduktion der Druckausgabe